Groundwater recharge/discharge patterns and groundwater–surface water interactions in a sedimentary aquifer along the River Kitinen in Sodankylä, northern Finland - Åberg, Susanne; Korkka-Niemi, Kirsti; Rautio, Anne Brita Kristina; Salonen, Veli-Pekka; Åberg, Annika (2019)
Areas of groundwater–surface water interaction in riverbanks and open mires are impor-tant habitats for groundwater-dependent species. In order to preserve these ecosystems, the planning and development of mining operations on such locations require a fundamental understanding of the groundwater discharge–recharge and flow patterns. In this study, 3D flow modelling and a TIR survey were used to define the groundwater discharge. Simul-taneously, the flow modelling and groundwater table fluctuation were used for defining groundwater recharge at a mining development site in northern Finland. The results indi-cated flow towards the River Kitinen and the discharge of groundwater in the banks of the river. The discharge also occurred within the mire area, which may provide suitable habitats for groundwater-dependent plant species. The modelling results and stable isotope variations indicated complex flow patterns and a potential groundwater connection from the Viiankiaapa mire through possible bedrock fractures to the river. Recharge mainly occurred in the sorted sediment accumulations of the riverbanks and partly also in the mire area. Peer reviewed